Pulmonary Embolism Following Laparoscopic Cholecystectomy - HIRO, Kanako; OKABAYASHI, Kazuhiro; AMANO, Homare; KAWAKITA, Mihoko; MARUYAMA, Kazuo (Nihon Rinshō Masui Gakkai shi, 2001)
We report a case of a 73-year-old female with two episodes of pulmonary embolism following laparoscopic cholecystectomy. Surgical embolectomy and anticoagulant therapy were successfully performed. Although the occurence of pulmpnary embolism following laparoscopic cholecystectomy itself is rare, patients with high-risk factors should be carefully observed to detect pulmonary embolism.